THE LINKAGE BETWEEN SPIRITUAL LEADERSHIP, EMPLOYEE SATISFACTION AND ORGANIZATIONAL COMMITMENT: INSIGHTS FROM PUBLIC SERVANTS - Tamrilinggau Tamrilinggau (Proceeding International Conference on Digital Education and Social Science, 2022)
Issues regarding workplace spirituality have received increased attention in the organizational sciences. The implications of workplace spirituality for leadership theory, research, and practice make this a fast growing area of a new research and inquiry by scholars. The article is aimed at examining a dynamic relationship between spiritual leadership, employee satisfaction and organizational commitment. For this purpose, we try to make a conclusion from many literatures. According to this literature study, it is predicted a positive and significant relationship between spritual leadership, employee satisfaction and organizational commitment. This article is needed to be examined in future, especially to test whether is there a relationship between spritual leadership, employee satisfaction and organizational commitment.